Interdependence of income between China and ASEAN-5 countries - Evan, Lau; Koon, Po Lee (Emerald, 2008)
Purpose – The purpose of the paper is to empirically examine the interdependence of income between China and ASEAN-5 countries by using the real gross domestic product (GDP). Besides answering this important policy question, the paper is also concerned with ascertaining the causal direction between China and the ASEAN-5 income. Design/methodology/approach – The paper resorts to the standard time series econometrics analysis. These includes the unit root, cointegration and the Granger causality tests in order to test the causal interplay and interdependence of income between ASEAN-5 and China for the estimation period from 1960 to 2003 obtained from the Penn World Table (PWT) 6.2. Findings – Empirical results are found to support the strong interdependence of income between China and ASEAN-5 countries. Further, the causality experiment suggests that China is the key factor in connecting (equilibrium point) the ASEAN-5 region, where China in one-way or another marks the resemblance of the income amongst these economies. Originality/value – The paper is of value in that it highlights the issue of interdependence of income especially in developing countries. With the increasing interest of economic integration around the globe especially the China-ASEAN Free Trade Area (CAFTA), the interdependence and synchronization movements of income between member countries is an important characteristic for suitability towards the regional common currency goal.